Sedimentation of 13 C-rich organic matter from Antarctic sea-ice algae: A potential indicator of past sea-ice extent - Gibson, JAE; Trull, T; Nichols, PD; Summons, RE; McMinn, A (Geological Society of America, 1999)
Organic matter collected in sediment traps at a nearshore marine site in Prydz Bay, East Antarctica, displayed a pronounced seasonal variation in carbon isotopes (expressed as 13C(OM)). Winter values were fairly constant near -20 before increasing to above -15 in response to inputs from sea-ice algae in early spring. Particulate organic matter obtained directly from sea-ice cores exhibited very high 13C(OM) values, typically -15 but as much as -8, much above the values of organic matter suspended in the water column below the sea ice. The sea-ice algae contributed ~20% of the annual flux of organic matter, and the 13C(OM) measurements from a sediment core at the site suggest that this value is representative of the recent past. All of these carbon isotopic compositions are considerably above the extremely 13C-depleted compositions (generally -25 to -30) that have been found in many other Antarctic and Southern Ocean studies. The elevated 13C(OM) values derive from considerable depletion of dissolved carbon dioxide and nutrients within the sea ice and to a lesser extent within stratified surface waters induced by melting sea ice. Thus, elevated 13C(OM) values in Southern Ocean sediment cores may indicate the presence of sea-ice-hosted algae, rather than temperature or surface CO2 pressure (pCO2) variations.